Modified colloidal binder as well as preparation and application thereof
By adding a modifier to the colloidal adhesive to change its fluid characteristics and polar functional group content, the problems of unstable settlement and gelation of the colloidal adhesive in a short period of time are solved, and its stability and bonding properties are significantly improved.
Patent Information
- Application Number
- CN202510063388.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The colloidal binder becomes unstable and gelled in a short period of time, resulting in poor aggregation stability, shortened shelf life, and affects the effect of uniform dispersion in iron concentrate.
Modifiers, such as anionic polyacrylamide, polyvinyl alcohol, alginic acid derivatives, etc., are added to the colloidal binder, and the stability and dispersion of the binder are improved by changing the polar functional group content and fluid characteristics.
It effectively improves the stability and bonding properties of colloidal adhesives, delays the growth rate of apparent viscosity, and improves the uniform dispersion and bonding effect in iron concentrate.
Smart Images

Figure CN119876592A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of pellet binders, and in particular to the technical field of colloid binders. Background Art
[0002] Binder is one of the indispensable raw materials for pellet production. The use of inorganic binder in pellet production has the disadvantages of large dosage, large residual amount, and reduced iron grade of pellet ore; although organic binder has small dosage, small residual amount, and does not reduce the iron grade of pellet, it has poor thermal stability and low strength of preheated pellets; composite binder has the advantages of both organic-inorganic binder, and can simultaneously solve the problems of large residual amount of inorganic binder and poor thermal performance of organic binder. Therefore, many pellet plants or binder plants are currently processing bentonite into organic composite bentonite through organic modification to improve its bonding performance and reduce the dosage of binder, and production practice has also achieved good application results. However, objectively, the preparation of organic composite bentonite is still based on bentonite, which is only formed by mixing bentonite with high molecular organic matter, and has not formed a true organic-inorganic composite. Its ratio is still high (~1.5%), and the inherent problems caused by inorganic binder residue and organic binder pyrolysis have not been fundamentally solved.
[0003] In view of the problems existing in the prior art, the present invention team discloses a colloidal pellet binder and its preparation and application in the Chinese invention patent with publication number CN 117305581 A, which has a wide range of raw materials, low price, simple preparation process, small amount of prepared binder product, good bonding performance, good raw material adaptability, low use cost, and the iron grade of the pellet is not affected. Add to the iron concentrate in the form of a concentrated solution, mix well and then make balls. However, in subsequent research and actual production applications, it is found that the colloidal binder prepared by some raw materials, with the extension of storage time, the micelles will quickly undergo obvious cross-linking overlap under the action of self-assembly, and the apparent viscosity continues to increase. It becomes a gel state in a relatively short time, resulting in poor aggregation stability of the colloidal binder, shortened shelf life, and an adverse effect on the uniform dispersion of the binder in the iron concentrate. Summary of the invention
[0004] In view of the problem of unstable sedimentation and gelation of colloidal binders in a short period of time, the first purpose of the present invention is to provide a method for modifying a colloidal binder, aiming to alleviate the problems of unstable sedimentation of the colloidal binder or its transformation into a gel state, and to improve its stability, uniformity, and dispersibility and adhesion in iron concentrate.
[0005] The second object of the present invention is to provide a modified colloidal binder prepared by the method and its application in the preparation of pellets / agglomerates.
[0006] The third object of the present invention is to provide green pellets or green agglomerates made using the modified colloidal binder of the present invention, and oxidized / reduced pellets / agglomerates obtained by further calcining.
[0007] The present invention aims to provide a colloidal binder. However, it was found in the early stage of research and development that inappropriate colloidal binders are not just a simple replacement of the material form compared to solid binders, ready-mixed solution binders, etc., and also face many unknown problems. For example, it is necessary to solve many technical problems such as system instability caused by the coagulation of colloidal binders, unsatisfactory rheological properties, and obvious attenuation of bonding and calcination performance with system instability (system sedimentation). In addition, it is also necessary to solve the gradual gelation problem faced by the pseudoplastic fluid properties of colloidal binders. In view of this technical problem, the present invention has proposed the following solutions after in-depth research:
[0008] A method for modifying a colloidal adhesive, comprising adding a modifier to the colloidal adhesive and mixing the mixture to obtain a modified colloidal adhesive;
[0009] The modifier includes three or more of anionic polyacrylamide, polyvinyl alcohol, alginic acid derivatives, fatty acid derivatives, cellulose derivatives, sulfonic acid derivatives, phosphoric acid derivatives, and amine derivatives;
[0010] The alginic acid derivative is at least one of alginic acid and its esters and salts;
[0011] The fatty acid derivative is at least one of a fatty acid and its esters and salts;
[0012] The cellulose derivative is at least one of cellulose and its grafted products and salts;
[0013] The sulfonic acid derivative is at least one of sulfonic acid and its esters and salts;
[0014] The phosphoric acid derivative is at least one of phosphoric acid, phosphonic acid and their esters and salts;
[0015] The amine derivative is at least one of amine and its derived amide, polymer and salt.
[0016] The present invention innovatively finds that adding the compatible modifier to the colloidal binder can change the fluid properties of the colloidal binder while increasing the content of polar functional groups in the colloidal binder, solve the problems of unstable sedimentation and gelation of the colloidal binder in a short period of time, improve the apparent viscosity of the binder, reduce the unstable sedimentation or excessive aggregation of the colloid, slow down the growth rate of the apparent viscosity, and improve its long-term storage stability.
[0017] The modifier is a monomer, a polymer or a precursor raw material for preparing each component containing the above raw materials.
[0018] Preferably, the salts in the modifier are at least one salt of ammonium, sodium and potassium of the anionic substances of each component.
[0019] Preferably, the alginate derivative is at least one of alginic acid, sodium alginate, ammonium alginate and propylene glycol alginate.
[0020] Preferably, the fatty acid derivative is C4~C 20 The mono- or poly-water-soluble carboxylic acid, ester and water-soluble salt thereof is preferably citric acid and water-soluble salt thereof, and further preferably at least one of sodium citrate and potassium citrate.
[0021] Preferably, the cellulose derivative is at least one of sodium carboxymethyl cellulose and hydroxyethyl cellulose.
[0022] Preferably, the sulfonic acid derivative is C6~C 20 The structure can be: Wherein at least one of R1 and R2 is a C6-C 20 The remaining substituents are C6~C 20 The alkyl group is H, M, wherein M is sodium / potassium, and more preferably at least one of sodium lignin sulfonate and sodium dodecylbenzene sulfonate.
[0023] Preferably, the phosphate derivative is an inorganic phosphate, an organic phosphonic acid, or an organic phosphate ester salt. The inorganic phosphate is at least one of sodium hexametaphosphate and sodium tripolyphosphate. The organic phosphate ester salt includes at least one of C1-C 20 Unit or polybasic phosphate / ester salt, the structural formula is Among the R1 and R2, at least one substituent is C1 to C 20 The remaining substituents are C1~C 20 The alkyl group or H, M, M is sodium / potassium, and is further preferably at least one of sodium glycerophosphate and xylose 1-phosphate.
[0024] Preferably, the amine derivatives include at least one C3-C 20 The unit may be at least one of a polybasic fatty amine, an amide and an amine-containing polymer or a salt thereof, and may further be at least one of polyaspartic acid and polyurethane.
[0025] The research of the present invention shows that the stability and effect of the colloidal binder can be effectively improved by combining the components of the modifier.
[0026] The modifier at least comprises anionic polyacrylamide;
[0027] Preferably, in the modifier, the content of anionic polyacrylamide is above 40wt%.
[0028] Preferably, the modifier further comprises at least polyvinyl alcohol;
[0029] Preferably, the content of polyvinyl alcohol in the modifier is above 20 wt%.
[0030] Preferably, the modifier comprises anionic polyacrylamide, polyvinyl alcohol and cellulose derivatives, wherein the weight ratio of polyacrylamide, polyvinyl alcohol and cellulose derivatives is 45-65:20-30:10-25; more preferably, the weight ratio of polyacrylamide, polyvinyl alcohol and cellulose derivatives is 55-65:24-26:14-16. Studies have shown that under the preferred ratio, the stability and modification effect of the colloidal binder can be effectively improved.
[0031] Preferably, the modifier comprises 5 or more of the above components. In the present invention, under this preferred combination, better stability and modification effect of the colloidal binder can be obtained.
[0032] Preferably, the modifier comprises anionic polyacrylamide, polyvinyl alcohol, cellulose derivatives, phosphoric acid derivatives and sulfonic acid derivatives. Further preferably, the weight ratio of anionic polyacrylamide, polyvinyl alcohol, cellulose derivatives, phosphoric acid derivatives and sulfonic acid derivatives is 40-50:25-35:5-15:5-15:1-10; further preferably, it is 43-47:28-32:8-12:8-12:4-6. Studies have shown that under the preferred ingredients and proportions, synergy can be further achieved, which helps to further improve the modification effect of the colloidal binder.
[0033] The modifier comprises anionic polyacrylamide, polyvinyl alcohol, fatty acid derivatives, sulfonic acid derivatives, and phosphoric acid derivatives. Further preferably, the weight ratio of anionic polyacrylamide, polyvinyl alcohol, fatty acid derivatives, sulfonic acid derivatives, and phosphoric acid derivatives is 40-50:25-35:5-15:5-15:1-10; further preferably, it is 45-49:26-30:6-10:10-14:4-6. Studies have shown that under the preferred ingredients and proportions, synergy can be further achieved, which helps to further improve the modification effect of the colloidal binder.
[0034] The present invention has found that the use of the preferred combined modifier of the present invention is helpful to further reduce the zeta potential of the colloidal binder and construct a steric hindrance effect, thereby delaying the sedimentation and gelation of the colloidal solution and improving its stability. At the same time, since the content of polar functional groups in the colloidal binder is increased, its adsorption on the mineral surface is improved, thereby improving the performance of the pellets.
[0035] In the present invention, the amount of the modifier is determined by comprehensively considering the processing cost and the use effect. The amount of the modifier added relative to the colloidal binder is preferably 1 to 5 g / L (more preferably 1.5 to 3 g / L). That is, based on the colloidal binder before modification, 1 to 5 g of the modifier is added per liter of the colloidal binder.
[0036] The present invention has found that, under the modification innovation of the modifier, further coordination with the components of the colloidal binder and the joint control of the preparation can further achieve synergy, further improve the modification effect of the modifier, and help to further synergistically improve the performance of the modified colloidal binder.
[0037] In the present invention, the modifier can be pre-mixed with the raw materials for preparing the colloidal binder, and the modifier can be added simultaneously during the preparation of the colloidal binder to make the two react together; and / or the modifier can be directly added to the colloidal binder product and fully mixed to obtain the modified colloidal binder.
[0038] Preferably, in the present invention, the colloidal binder is prepared by mechanically activating raw materials containing humic acid substances and clay components with alkaline substances in water.
[0039] The colloidal adhesive of the present invention can be prepared according to CN 117305581 A.
[0040] In the present invention, the fluid property of the colloidal binder is pseudoplastic fluid, and the viscosity of the colloidal binder is 1s at 25°C. -1 The apparent viscosity is 2000~30000mPa·s.
[0041] The present invention has found that by physically and chemically activating raw materials containing humic acid substances and clay components and alkaline substances under mechanical action, and further coordinating the humic acid substances, total acid group content, clay components, water, alkaline substance dosage and temperature in the mechanical activation stage in the raw materials, a colloidal binder with good rheological properties and good system stability can be obtained, and the colloidal binder can obtain better green ball performance and roasting performance at a lower dosage. Combining the colloidal binder obtained by the preparation process with the modifier of the present invention is conducive to synergy and helps to further improve the modification effect.
[0042] In the present invention, the raw material can be a coal-based raw material containing the humic acid substances and clay content requirements, preferably at least one of peat, lignite or weathered coal containing the humic acid substances and clay content requirements. Studies have shown that using coal-based raw materials that meet the humic acid substances, total acid groups, and clay content requirements of the present invention as raw materials helps to further improve its synergy with mechanical activity, and further cooperates with the modification of the modifier of the present invention, which helps to further improve the system stability, adhesion and pellet roasting performance of the obtained colloidal binder.
[0043] The present invention also includes a modified colloid binder obtained by the method for modifying the colloid binder.
[0044] In the present invention, the fluid property of the modified colloidal binder is pseudoplastic fluid, and the fluid property of the modified colloidal binder is pseudoplastic fluid. -1 The apparent viscosity is 2000~30000mPa·s;
[0045] Preferably, calculated on a dry basis, the modified colloidal binder has a soluble content of 50 to 140 g / L, an insoluble content of 40 to 80 g / L, and a modifier content of 1 to 5 g / L.
[0046] The present invention also provides an application of the modified colloidal binder, which is used as a binder for balling or briquetting mineral powder to obtain green pellets or green agglomerates, which are further oxidized and roasted to obtain oxidized pellets, or reduced and roasted to obtain reduced pellets.
[0047] Further preferably, the modified colloidal binder is uniformly mixed with the mineral powder by atomization spraying, and the mixture is subjected to high-pressure roller milling to form balls or briquettes to obtain green pellets or green agglomerates; and further subjected to oxidative roasting or reduction roasting to produce oxidized pellets / agglomerates or reduced pellets / agglomerates;
[0048] Preferably, the modified colloidal binder is added in an amount of 0.5% to 3.0% (or further 1 to 1.5%) of the mass of the mineral powder, and the dry mass of the binder is 0.1% to 0.6% of the mass of the mineral powder.
[0049] Beneficial Effects
[0050] (1) In view of the coagulation and gelation problems faced by colloidal adhesives, the present invention innovatively finds that the use of the modifier to modify the colloidal adhesive can effectively improve the stability of the colloidal adhesive, and improve its bonding performance and performance stability.
[0051] (2) The use of the preferred combination of modifiers can achieve synergy and help further improve the stability and performance stability of the colloidal binder.
[0052] (3) The adding method is simple and does not require additional colloidal adhesive production equipment.
[0053] (4) Small amount of addition and low cost. The amount of raw material added in the present invention is only 1-5 g / L, and the production cost per ton of binder only increases by 6-30 yuan. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 The graph shows the apparent viscosity change of the colloid adhesive in each embodiment and comparative example after being placed for different time periods. DETAILED DESCRIPTION
[0055] The following examples are intended to further illustrate the present invention rather than to limit the scope of protection of the present invention.
[0056] The anionic polyacrylamide (APAM) used in the embodiment is a Maclean AR pure reagent, Mw=5 million, CAS No. 9003-05-8; polyvinyl alcohol (PVA) is a Maclean 98% hydrolyzed reagent, Mw=13000-23000, CAS No. 9002-89-5; sodium hexametaphosphate is a Maclean 65% reagent, CAS No. 10124-56-8.
[0057] Comparative Example 1
[0058] The colloidal binder was prepared by using the method and raw materials of Example 1 in the publication number CN 117305581 A, wherein the soluble matter content was 92.6 g / L and the insoluble matter content was 67.1 g / L. The total acid group content of the colloidal binder on a dry basis was 4.688 mmol / g, the pH was 11.64, the zeta potential was -47.0 mV, and after standing for 2 days, the zeta potential was 0.04477 mV at 25°C for 1 s. -1 The apparent viscosity was 5855 mPa·s at a shear rate of 1.5 %. After standing for 14 days, the viscosity was 1.5 % at 25°C. -1 The apparent viscosity was measured to be 20670 mPa·s at a shear rate of .
[0059] The prepared colloidal binder is used to prepare oxidized pellets, with a colloidal binder dosage of 1%. After being fully mixed, it is subjected to high-pressure roller milling and pelletization. The pelletization time is 12 minutes, and the green pellet size is 14-16 mm. The green ball drop strength is 15.2 times / (0.5m), the compressive strength is 31.6N / p, and the burst temperature is 570℃; under the conditions of preheating at 880℃ for 16 minutes and roasting at 1280℃ for 16 minutes, the preheated pellet strength is 572N / p, and the roasted pellet strength is 3352N / p.
[0060] Example 1
[0061] The colloidal binder was prepared by using the method and raw materials of Comparative Example 1. During the preparation of the binder, a modifier consisting of 60 wt% anionic polyacrylamide, 25 wt% polyvinyl alcohol, and 15 wt% sodium carboxymethyl cellulose was added to the mixed raw material system for preparing the colloidal binder. The added content of the modifier was 2.7 g / L. The total acid content of the colloidal binder on a dry basis was 4.715 mmol / g, the pH was 11.76, and the zeta potential was -51.2 mV. After standing for 2 days, the zeta potential of the colloidal binder was 0.0447 W / L at 25°C for 1 s. -1 The apparent viscosity was 5352 mPa·s at a shear rate of 1.5. -1 The apparent viscosity was measured to be 12598 mPa·s at a shear rate of .
[0062] The prepared colloidal binder is used to prepare oxidized pellets, with a colloidal binder dosage of 1%. After being fully mixed, it is subjected to high-pressure roller milling and pelletization. The pelletization time is 12 minutes, and the green pellet size is 14-16 mm. The green ball drop strength is 17.8 times / (0.5m), the compressive strength is 31.0N / p, and the burst temperature is 550℃; under the conditions of preheating at 880℃ for 16 minutes and roasting at 1280℃ for 16 minutes, the preheated pellet strength is 556N / p, and the roasted pellet strength is 3436N / p.
[0063] The prepared colloidal binder was used to prepare reduction agglomerates. The colloidal binder was added in an amount of 2.5%. After being fully mixed, it was pressed into blocks after being passed through a high-pressure roller mill. The blocks were formed by a double roller and then dried at a pressure of 2200N / cm 2 , the particle size of the agglomerate is 20cm. The drop strength of the wet agglomerate is 25.6 times / (0.5m), the compressive strength is 115.8N / p, the drop strength of the dry agglomerate is >50 times / (0.5m), and the compressive strength is 3213N / p. After reduction at 1050℃ for 1h, the reduction degree is 86.9% and the metallization rate is 81.3%.
[0064] It can be seen from Comparative Example 1 and Example 1 that the use of the modifier of the present invention can improve the performance of the colloidal binder, thereby improving multiple properties of the subsequent pellets, especially effectively improving the raw pellet performance.
[0065] Example 2
[0066] Compared with Example 1, the main difference is that the addition method of the modifier is different, specifically:
[0067] The colloidal binder was prepared by using the method and raw materials of Comparative Example 1. A modifier consisting of 60 wt% anionic polyacrylamide, 25 wt% polyvinyl alcohol, and 15 wt% sodium carboxymethyl cellulose was added to the colloidal binder (colloidal binder a) that had been left to stand for 2 days and mixed evenly. The amount of modifier added was 2.7 g / L. The total acid content of the colloidal binder on dry basis was 4.632 mmol / g, the pH was 11.72, the zeta potential was -49.6 mV, and the zeta potential was -49.6 mV at 25°C for 1 s. -1 The apparent viscosity was 4625 mPa·s at a shear rate of 1.5. -1 The apparent viscosity was measured to be 14293 mPa·s at a shear rate of .
[0068] The prepared colloidal binder is used to prepare oxidized pellets, with a colloidal binder dosage of 1%. After being fully mixed, it is subjected to high-pressure roller milling and pelletization. The pelletization time is 12 minutes, and the green pellet size is 14-16 mm. The green ball drop strength is 19.4 times / (0.5m), the compressive strength is 30.6N / p, and the burst temperature is 550℃; under the conditions of preheating at 880℃ for 16 minutes and roasting at 1280℃ for 16 minutes, the preheated pellet strength is 532N / p, and the roasted pellet strength is 3488N / p.
[0069] It can be seen from Examples 1 and 2 that, no matter at which stage, the use of the modifier described in the present invention can improve the performance of the colloidal binder, especially by involving the modifier in the in-situ co-reaction synthesis process of the colloidal binder, which can further optimize the colloidal network and help to further improve its stability and the performance of the subsequently prepared pellets, especially effectively improve the raw pellet performance.
[0070] Example 3
[0071] Compared with Example 1, the main difference is that the type of modifier is changed, specifically:
[0072] The colloidal binder was prepared by using the method and raw materials of Comparative Example 1. A modifier consisting of 45 wt% anionic polyacrylamide, 30 wt% polyvinyl alcohol, 10 wt% sodium carboxymethyl cellulose, 10 wt% sodium hexametaphosphate, and 5 wt% sodium dodecylbenzene sulfonate was added to the starting raw material system for the synthesis of the colloidal binder. The amount of the modifier added was 2.5 g / L. The total acid content of the colloidal binder on a dry basis was 4.783 mmol / g, the pH was 11.79, the zeta potential was -52.7 mV, and after standing for 2 days, the zeta potential was -52.7 mV at 25°C for 1 s. -1 The apparent viscosity was 3680 mPa·s at a shear rate of 1.5. -1 The apparent viscosity was measured to be 5745 mPa·s at a shear rate of .
[0073] The prepared colloidal binder is used to prepare oxidized pellets, with a colloidal binder dosage of 1%. After being fully mixed, it is subjected to high-pressure roller milling and pelletization. The pelletization time is 12 minutes, and the green pellet size is 14-16 mm. The green ball drop strength is 20.5 times / (0.5m), the compressive strength is 31.5N / p, and the burst temperature is 560℃; under the conditions of preheating at 880℃ for 16 minutes and roasting at 1280℃ for 16 minutes, the preheated pellet strength is 544N / p, and the roasted pellet strength is 3431N / p.
[0074] Example 4
[0075] Compared with Example 1, the main difference is that the type of modifier is changed, specifically:
[0076] The colloidal binder was prepared by using the method and raw materials of Comparative Example 1. A modifier consisting of 47 wt% anionic polyacrylamide, 28 wt% polyvinyl alcohol, 8 wt% sodium citrate, 12 wt% sodium hexametaphosphate, and 5 wt% sodium dodecylbenzene sulfonate was added to the starting raw material system for the synthesis of the colloidal binder. The amount of the modifier added was 2.4 g / L. The total acid content of the colloidal binder on a dry basis was 4.736 mmol / g, the pH was 11.78, the zeta potential was -52.3 mV, and after standing for 2 days, the zeta potential was -52.3 mV at 25°C for 1 s. -1 The apparent viscosity was 3892 mPa·s at a shear rate of 1.5. -1 The apparent viscosity was measured to be 6250 mPa·s at a shear rate of .
[0077] The prepared colloidal binder is used to prepare oxidized pellets, with a colloidal binder dosage of 1%. After being fully mixed, it is subjected to high-pressure roller milling and pelletization. The pelletization time is 12 minutes, and the green pellet size is 14-16 mm. The green ball drop strength is 20.1 times / (0.5m), the compressive strength is 30.6N / p, and the burst temperature is 560℃; under the conditions of preheating at 880℃ for 16 minutes and roasting at 1280℃ for 16 minutes, the preheated pellet strength is 530N / p, and the roasted pellet strength is 3377N / p.
[0078] It can be seen from Examples 1, 3 and 4 that the use of the five-component combination of modifiers can achieve excellent colloidal binder modification effects at lower modifier dosages, and can especially effectively improve green ball performance.
[0079] Comparative Example 2
[0080] Compared with Example 4, the main difference is that only a single type of modifier is added, and the experimental groups are:
[0081] A: Only anionic polyacrylamide was added, and the amount of modifier added was 2.4 g / L.
[0082] The total acid content of the colloid binder on dry basis was 4.714mmol / g, the pH was 11.70, the zeta potential was -51.7mV, and after standing for 2 days, the zeta potential was -51.7mV at 25℃ for 1s. -1 The apparent viscosity was 5756 mPa·s at a shear rate of 1.5 %. After standing for 14 days, the viscosity was 1.5 % at 25°C. -1 The apparent viscosity was measured to be 18650 mPa·s at a shear rate of , and the viscosity change effect was not obvious.
[0083] B: Only polyvinyl alcohol was added, and the amount of modifier added was 2.4 g / L.
[0084] The total acid content of the colloid binder on dry basis was 4.602mmol / g, the pH was 11.74, the ζ potential was -51.8mV, and after standing for 2 days, the zeta potential was 0.0447mV at 25℃ for 1s. -1 The apparent viscosity was 5582 mPa·s at a shear rate of 1.5. -1 The apparent viscosity was measured to be 20602 mPa·s at a shear rate of , and the viscosity change effect was not obvious.
[0085] C: Only sodium hexametaphosphate was added, and the amount of modifier added was 2.4 g / L.
[0086] The total acid content of the colloid binder on dry basis was 4.652mmol / g, the pH was 11.66, the ζ potential was -42.0mV, and after standing for 2 days, the zeta potential was 0.0447mV at 25℃ for 1s. -1 The apparent viscosity was 3055 mPa·s at a shear rate of 1.04. -1 The apparent viscosity was 1890 mPa·s at a shear rate of 1.5, and the binder partly precipitated. The prepared colloidal binder was used to prepare oxidized pellets. The colloidal binder was added in an amount of 1%. After being fully mixed, it was passed through a high-pressure roller mill to form pellets. The pelletizing time was 12 minutes, and the green pellet size was 14-16 mm. The green ball drop strength was 15.0 times / (0.5m), the compressive strength was 29.7 N / p, and the burst temperature was 560°C; under the conditions of preheating at 880°C for 16 minutes and roasting at 1280°C for 16 minutes, the preheated pellet strength was 525 N / p, and the roasted pellet strength was 3286 N / p.
[0087] Comparative Example 3
[0088] Compared with Example 4, the main difference is that the combination of modifiers is not within the preferred range, and the experimental groups are:
[0089] A: 60% anionic polyacrylamide + 40% sodium carboxymethyl cellulose, the amount of modifier added is 2.4g / L.
[0090] The total acid content of the colloidal binder on a dry basis was 4.828 mmol / g, the pH was 11.85, the ζ potential was -51.5 mV, and after standing for 2 days, the zeta potential was 0.0447 W / mV at 25 °C for 1 s. -1 The apparent viscosity was 5520 mPa·s at a shear rate of 1.5. After standing for 14 days, the viscosity was 25°C at 1s -1 The apparent viscosity was measured to be 17365 mPa·s at a shear rate of , and the viscosity change effect was not obvious.
[0091] B: 50% sodium dodecylbenzene sulfonate + 50% sodium tripolyphosphate, the amount of modifier added is 2.4g / L.
[0092] The total acid content of the colloidal binder on a dry basis was 4.656 mmol / g, the pH was 11.66, the ζ potential was -48.0 mV, and after standing for 2 days, the zeta potential was 0.0447 mV at 25 °C for 1 s. -1 The apparent viscosity was 6020 mPa·s at a shear rate of 1.5. After standing for 14 days, the viscosity was 25°C at 1s -1 The apparent viscosity was measured to be 23845 mPa·s at a shear rate of , and the viscosity change effect was not obvious.
[0093] Comparative Example 4
[0094] Compared with Comparative Example 1, the main difference is that the raw materials of the colloidal binder are changed, specifically:
[0095] The colloidal binder was prepared by using the method and raw materials of Example 5 in the publication number CN 117305581 A, wherein the soluble matter content was 81.0 g / L and the insoluble matter content was 107.3 g / L. The total acid group content of the colloidal binder on a dry basis was 3.664 mmol / g, the pH was 11.86, the zeta potential was -46.2 mV, and after standing for 2 days, the zeta potential was -46.2 mV at 25°C for 1 s. -1 The apparent viscosity was 3205 mPa·s at a shear rate of 1.38.5 mPa·s. After standing for 14 days, the viscosity was 25°C at 1 s -1 The apparent viscosity was measured to be 29878 mPa·s at a shear rate of .
[0096] The prepared colloidal binder is used to prepare oxidized pellets, with a colloidal binder dosage of 1%. After being fully mixed, it is subjected to high-pressure roller milling and pelletization. The pelletization time is 12 minutes, and the green pellet size is 14-16 mm. The green ball drop strength is 31.7 times / (0.5m), the compressive strength is 35.9N / p, and the burst temperature is 570℃; under the conditions of preheating at 880℃ for 16 minutes and roasting at 1280℃ for 16 minutes, the preheated pellet strength is 613N / p, and the roasted pellet strength is 3545N / p.
[0097] Example 5
[0098] The colloidal binder was prepared by using the method and raw materials of Comparative Example 4, and a modifier consisting of 60wt% anionic polyacrylamide, 25wt% polyvinyl alcohol, and 15wt% sodium carboxymethyl cellulose was added to the colloidal binder at the same time, and the modifier addition content was 2.7g / L. The total acid content of the colloidal binder on a dry basis was 3.824mmol / g, the pH was 11.89, and the zeta potential was -48.4mV. After standing for 2 days, the zeta potential of the colloidal binder was 0.04477mol / g at 25℃ for 1s. -1 The apparent viscosity was 2303 mPa·s at a shear rate of 1.5. After standing for 14 days, the viscosity was 2303 mPa·s at a shear rate of 1.5. -1 The apparent viscosity was measured to be 8592 mPa·s at a shear rate of .
[0099] The prepared colloidal binder is used to prepare oxidized pellets, with a colloidal binder dosage of 1%. After being fully mixed, it is subjected to high-pressure roller milling and pelletization. The pelletization time is 12 minutes, and the green pellet size is 14-16 mm. The green ball drop strength is 33.6 times / (0.5m), the compressive strength is 35.2N / p, and the burst temperature is 550℃; under the conditions of preheating at 880℃ for 16 minutes and roasting at 1280℃ for 16 minutes, the preheated pellet strength is 580N / p, and the roasted pellet strength is 3502N / p.
Claims
1. A method for modifying a colloidal binder, characterized in that: Adding a modifier to the colloidal adhesive and mixing the mixture to obtain a modified colloidal adhesive; The modifier includes three or more of anionic polyacrylamide, polyvinyl alcohol, alginic acid derivatives, fatty acid derivatives, cellulose derivatives, sulfonic acid derivatives, phosphoric acid derivatives, and amine derivatives; The alginic acid derivative is at least one of alginic acid and its esters and salts; The fatty acid derivative is at least one of a fatty acid and its esters and salts; The cellulose derivative is at least one of cellulose and its grafted products and salts; The sulfonic acid derivative is at least one of sulfonic acid and its esters and salts; The phosphoric acid derivative is at least one of phosphoric acid, phosphonic acid and their esters and salts; The amine derivative is at least one of amine and its derived amide, polymer and salt.
2. The method for modifying a colloidal adhesive according to claim 1, characterized in that: The modifier is each component or a precursor raw material for preparation; the salt derived from each component is at least one of an ammonium salt, a sodium salt, and a potassium salt; Preferably, the alginic acid derivative is at least one of alginic acid, sodium alginate, ammonium alginate and propylene glycol alginate; Preferably, the fatty acid derivative is C4~C 20 A unit or polybasic water-soluble carboxylic acid, ester and water-soluble salt thereof, more preferably citric acid and water-soluble salt thereof, and further preferably at least one of sodium citrate and potassium citrate; Preferably, the cellulose derivative is at least one of sodium carboxymethyl cellulose and hydroxyethyl cellulose; Preferably, the sulfonic acid derivative is C6~C 20 A unit or multi-unit water-soluble sulfonic acid or sulfonate, more preferably at least one of sodium lignin sulfonate and sodium dodecylbenzene sulfonate; Preferably, the phosphate derivative is an inorganic phosphate, an organic phosphonic acid, or an organic phosphate ester salt. The inorganic phosphate is at least one of sodium hexametaphosphate and sodium tripolyphosphate. The organic phosphate ester salt includes at least one of C1-C 20 A unit or polybasic phosphate / ester salt, further preferably at least one of sodium glycerophosphate and xylose 1-phosphate; Preferably, the amine derivatives include at least one C3-C 20 The unit may be at least one of a polybasic fatty amine, an amide and an amine-containing polymer or a salt thereof, and may further be at least one of polyaspartic acid and polyurethane.
3. The method for modifying a colloidal adhesive according to claim 1, characterized in that: The modifier at least comprises anionic polyacrylamide; Preferably, in the modifier, the content of anionic polyacrylamide is above 40wt%.
4. The method for modifying a colloidal adhesive according to claim 3, characterized in that: The modifier further comprises at least polyvinyl alcohol; Preferably, the content of polyvinyl alcohol in the modifier is above 20 wt%.
5. The method for modifying a colloid-type adhesive according to any one of claims 1 to 4, characterized in that: The modifier comprises anionic polyacrylamide, polyvinyl alcohol and cellulose derivatives, wherein the weight ratio of polyacrylamide, polyvinyl alcohol and cellulose derivatives is 45-65:20-30:10-25; further preferably, the weight ratio of polyacrylamide, polyvinyl alcohol and cellulose derivatives is 55-65:24-26:14-16.
6. The method for modifying a colloid-type adhesive according to any one of claims 1 to 4, characterized in that: The modifier comprises 5 or more of the above ingredients; Preferably, the modifier comprises anionic polyacrylamide, polyvinyl alcohol, cellulose derivatives, phosphoric acid derivatives and sulfonic acid derivatives; More preferably, the weight ratio of anionic polyacrylamide, polyvinyl alcohol, cellulose derivatives, phosphoric acid derivatives and sulfonic acid derivatives is 40-50:25-35:5-15:5-15:1-10; more preferably 43-47:28-32:8-12:8-12:4-6; Alternatively, the modifier comprises anionic polyacrylamide, polyvinyl alcohol, fatty acid derivatives, sulfonic acid derivatives and phosphoric acid derivatives; More preferably, the weight ratio of anionic polyacrylamide, polyvinyl alcohol, fatty acid derivatives, sulfonic acid derivatives and phosphoric acid derivatives is 40-50:25-35:5-15:5-15:1-10; more preferably 45-49:26-30:6-10:10-14:4-6.
7. The method for modifying a colloid-type adhesive according to any one of claims 1 to 6, characterized in that: The amount of the modifier added to the colloid binder is 1 to 5 g / L, and more preferably 1.5 to 3 g / L.
8. The method for modifying a colloidal adhesive according to claim 1, wherein: The modifier is pre-mixed with the raw materials for preparing the colloidal binder, and the modifier is added simultaneously during the preparation process of the colloidal binder to make the two react together to obtain the modified colloidal binder; and / or the modifier is directly added to the colloidal binder product and fully mixed to obtain the modified colloidal binder.
9. A modified colloidal binder prepared by the method according to any one of claims 1 to 8; Preferably, the fluid property of the modified colloid type binder is pseudoplastic fluid, and the binder colloid is -1 The apparent viscosity is 2000~30000mPa·s; Preferably, calculated on a dry basis, the modified colloidal binder has a soluble content of 50 to 140 g / L, an insoluble content of 40 to 80 g / L, and a modifier content of 1 to 5 g / L.
10. Use of a modified colloidal adhesive prepared by the method according to any one of claims 1 to 8, characterized in that: It is used as a binder for balling or briquetting of mineral powder to obtain green pellets or green briquettes, which are further oxidized and roasted to obtain oxidized pellets, or reduced and roasted to obtain reduced pellets; Preferably, the modified colloidal binder is added in an amount of 0.5% to 3.0% of the mass of the mineral powder, and the dry mass of the binder is 0.1% to 0.6% of the mass of the mineral powder.
Citation Information
Patent Citations
Additive with applications in construction chemistry
CN101268028A
Dye Aqueous Dispersion
CN102300937A
Pellet additive and preparation method thereof
CN104004906A
Colloid pellet binder and preparation and application thereof
CN117305581A
Granulating agent for powdery metallic raw material and wet granulating method
JP2000178662A